2019
DOI: 10.1002/qua.25925
|View full text |Cite
|
Sign up to set email alerts
|

Exploring point defects in hexagonal boron‐nitrogen monolayers

Abstract: A comprehensive theoretical study of selected point defects for a monolayer of hexagonal boron nitride (h‐BN) is presented. Two‐dimensional structures were simulated through large h‐BN molecular clusters and used to examine various defects, like: atom vacancies, atom substitutions, or distortions of the hexagonal lattice. Since carbon contaminations are very common in the h‐BN technology, a particular attention has been paid to carbon impurities. The calculations of IR spectra for the doped molecular clusters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 54 publications
3
42
2
1
Order By: Relevance
“…an anti-site nitrogen-vacancy (nitrogen occupies a boron site, and there is a vacancy at the nitrogen site) [36]. In the framework of quantum computing, group analysis along with DFT calculations demonstrated that the neutral paramagnetic carbon defect C B V N could be a valid candidate for spin coherent manipulation and qubit, as well as C N V B [39,40,41]. Recently, Weston et al attributed the single-photon emission in the UV and at about 2 eV to carbon substituting nitrogen and interstitial centers, respectively [42].…”
Section: Understanding Bn Materials By Theoretical Calculationsmentioning
confidence: 99%
“…an anti-site nitrogen-vacancy (nitrogen occupies a boron site, and there is a vacancy at the nitrogen site) [36]. In the framework of quantum computing, group analysis along with DFT calculations demonstrated that the neutral paramagnetic carbon defect C B V N could be a valid candidate for spin coherent manipulation and qubit, as well as C N V B [39,40,41]. Recently, Weston et al attributed the single-photon emission in the UV and at about 2 eV to carbon substituting nitrogen and interstitial centers, respectively [42].…”
Section: Understanding Bn Materials By Theoretical Calculationsmentioning
confidence: 99%
“…[ 23 ] showed that the 4.1 eV luminescence peak could be caused by the carbon dimer defect (C B C N ), which is a complex formed by two impurity carbon atoms on nearest-neighbor sites in the h-BN lattice. Another theoretical study using quantum chemistry calculations on h-BN monolayer suggested that carbon clusters from two to four atoms such as C B C N , C 4 cis , and C 4 trans defects give luminescence in the range of 3.9 to 4.8 eV [ 24 ]. Thus, the sharp emission lines observed in the UV region could be related to carbon defects which are generated during the annealing process.…”
Section: Resultsmentioning
confidence: 99%
“…Nothing specific is observed except the rise of a series of peaks at 4.1 eV when growth conditions depart from using ultra pure B and N precursor. These peaks were initially attributed to carbon incorporation in the lattice [135] but this interpretation is no longer shared [136][137][138][139][140][141][142][143]. It is obvious that it is related to a probable influence of the impurities of the precursors that impact the formation of a perfect crystal or contaminate it.…”
Section: Defects At 4 Evmentioning
confidence: 99%